RFEA Measurements of High-Energy Electrons in a Helicon Plasma Device with Expanding Magnetic Field - Gulbrandsen, Njål; Fredriksen, Åshild (Frontiers in Physics, 2017)
In the inductively coupled plasma of the Njord helicon device we have, for the same parameters as for which an ion beam exists, measured a downstream population of high-energy electrons emerging from the source. Separated measurements of energetic tail electrons was carried out by Retarding Field Energy Analyzer (RFEA) with a grounded entrance grid, operated in an electron collection mode. In a radial scan with the RFEA pointed toward the source, we found a significant population of high-energy electrons just inside the magnetic field line mapping to the edge of the source. A second peak in high-energy electrons density was observed in a radial position corresponding to the radius of the source. Also, throughout the main column a small contribution of high-energy electrons was observed. In a radial scan with a RFEA biased to collect ions a localized increase in the plasma ion density near the magnetic field line emerging from the plasma near the wall of the source was observed. This is interpreted as a signature of high-energy electrons ionizing the neutral gas. Also, a dip in the floating potential of a Langmuir probe is evident in this region where high-energy electrons is observed.